2015
DOI: 10.1016/j.fm.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

YEAST dynamics during the natural fermentation process of table olives ( Negrinha de Freixo cv.)

Abstract: a b s t r a c tYeast population and dynamics associated to spontaneous fermentation of green table olives Negrinha de Freixo cv. were evaluated. Olives and brine samples were taken at different fermentation times, and yeast were enumerated by standard plate count and identified by sequencing of the internal transcribed spacer (ITS) region of the nuclear ribosomal DNA (rDNA). Saccharomyces cerevisiae was the most frequent, followed by Candida tropicalis, Pichia membranifaciens and Candida boidini, representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…These changes were not observed in benign hyperplastic lesions, suggesting that the presence of this enzyme might be worth in the diagnosis of premalignant lesions of hamster oral mucosa (Pereira et al, 2015). Consistent with the previous results, findings of present study revealed that intense level of activity of LDH was detected in the epithelium layer around the keratotic crypts in addition to basal cell hyperplasia after 3 weeks of DMBA injections.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These changes were not observed in benign hyperplastic lesions, suggesting that the presence of this enzyme might be worth in the diagnosis of premalignant lesions of hamster oral mucosa (Pereira et al, 2015). Consistent with the previous results, findings of present study revealed that intense level of activity of LDH was detected in the epithelium layer around the keratotic crypts in addition to basal cell hyperplasia after 3 weeks of DMBA injections.…”
Section: Discussionsupporting
confidence: 91%
“…Many previous studies confirmed the increase of serum LDH levels in both oral premalignant and malignant lesions and have shown that serum LDH estimation may serve as a valuable biochemical marker of malignancy (Pereira et al, 2015). In current study injection of vitamin C in addition to DMBA resulted in an earlier increase the level of LDH in comparison with that obtained in groups C in addition to DMBA resulted in an earlier increase the level of LDH in comparison with that obtained in groups injected with DMBA alone which confirmed the promotional role of vitamin C on the development of oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 66%
“…Arroyo-Lopez et al (2008) referred presence of C. boidinii both in green and black directly brined olives. Farris et al (1986) isolated some strains of C. boidinii in directly brined black olives, while Pereira et al (2015) reported recently the presence of this species in the spontaneous fermentation of green olives.…”
Section: Molecular Study Of the Yeast Population In Bosana Olive Brinesmentioning
confidence: 99%
“…Yeasts are commonly isolated from different foods, including table olives (Bautista-Gallego et al, 2011;Pereira, Ramalhosa, Borges, Pereira, & Baptista, 2015), and several strains were used as biocontrol agents against mold growth in apples, grain, and sorghum (Ädel Druvefors & Schnürer, 2005;Rosa, Tauk-Tornisielo, Rampazzo, & Ceccato-Antonini, 2010;Vero, Mondino, Burgueno, Soubes, & Wisniewski, 2002;Zhang, Spadaro, Garibaldi, & Gullino, 2011). They are considered important microorganisms in table olive fermentation for their technological properties and different beneficial effects for human health (Arroyo-López et al, 2012).…”
Section: Practical Applicationsmentioning
confidence: 99%